Proteomic and immunoproteomic insights into the exoproteome of Actinobacillus pleuropneumoniae, the causative agent of porcine pleuropneumonia. (November 2022) - Stancheva, Stelli G.; Frömbling, Janna; Sassu, Elena L.; Hennig-Pauka, Isabel; Ladinig, Andrea; Gerner, Wilhelm; Grunert, Tom; Ehling-Schulz, Monika
Abstract: Porcine pleuropneumonia caused by Actinobacillus pleuropneumoniae affects pig health status and the swine industry worldwide. Despite the extensive number of studies focused on A. pleuropneumoniae infection and vaccine development, a thorough analysis of the A. pleuropneumoniae exoproteome is still missing. Using a complementary approach of quantitative proteomics and immunoproteomics we gained an in-depth insight into the A. pleuropneumoniae serotype 2 exoproteome, which provides the basis for future functional studies. Label-free liquid chromatography-tandem mass spectrometry (LC-MS/MS) revealed 593 exoproteins, of which 104 were predicted to be virulence factors. The RTX toxins ApxIIA and ApxIIIA -were found to be the most abundant proteins in the A. pleuropneumoniae serotype 2 exoproteome. Furthermore, the ApxIVA toxin was one of the proteins showing the highest abundance, although ApxIVA is commonly assumed to be expressed exclusively in vivo . Our study revealed several antigens, including proteins with moonlight functions, such as the elongation factor (EF)-Tu, and proteins linked to specific metabolic traits, such as the maltodextrin-binding protein MalE, that warrant future functional characterization and might present potential targets for novel therapeutics and vaccines. Our Ig-classes specific serological proteome analysis (SERPA) approach allowed us to explore the development of the host humoral immune response over the course of the infection. These SERPAs pinpointed proteins that might play a key role in virulence and persistence and showed that the immune response to the different Apx toxins is distinct. For instance, our results indicate that the ApxIIIA toxin has properties of a thymus-independent antigen, which should be studied in more detail. Highlights: Most comprehensive exoproteome analysis of Actinobacillus pleuropneumoniae . Actinobacillus pleuropneumoniae exoproteome comprises an array of virulence factors. Proof of in vitro expression of the RTX toxin ApxIV facilitate functional studies. Portray of the immunogenic proteins within the bacterial exoproteome. Dynamics of host immune adaptation revealed by Ig-class specific immunoproteomics.